Cover, Content, and Editorial Note from Borneo J Pharm Vol. 1 No. 2 November 2018 - Chief Editor of Borneo J Pharm (Borneo Journal of Pharmacy, 2018)
Alhamdulillahirabbil ‘alamin. The next edition of Borneo Journal of Pharmacy (Borneo J Pharm), has been published in November 2018. This journal aims to publish high-quality articles dedicated to all aspects of the latest outstanding developments in the field but not limited to Pharmacology-Toxicology, Pharmacognosy-Phytochemistry, Pharmaceutical, Analytical Pharmacy-Medicinal Chemistry, Natural Product Development, Clinical-Community Pharmacy, Management Pharmacy, and other Pharmacy aspects. It was first published online in May 2018 using Open Journal System (OJS) 3.1 platform with e-ISSN 2621-4814 by url http://journal.umpalangkaraya.ac.id/index.php/bjop. This edition contains eight articles consisting of Pharmacology-Toxicology, Pharmaceutical, Analytical Pharmacy-Medicinal Chemistry, Natural Product Development, and Clinical-Community Pharmacy topics. Editorial boards are fully aware that there is still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next versions. The editorial board would like to thank the University, all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors of the materials, could re-participate for the success of the publication in the next edition in May 2019.